الغطاء النباتي الرعوي بغابة سيدي إمحمد شمال مدينة الأبيار بالجبل الأخضر – ليبيا - عبد الحميد الزربي (Scientific Journal of University of Benghazi, 2021)
The Sidi Imhamed forest (north of Al-Ebyar city) in Al Jabal al Akhdar considered an important forage source for domestic and wild animals because it contains a variety of important trees, shrubs, perennial and annual herbs, which represent the rangeland of the forest. The aim of this study is to identify the most important rangeland species and their importance for domestic animals. The results revealed that there are 76 species of flowering plants; recorded 42 genera belong to 21 families. Only one family belongs to Gymnosperms, represented by one genus and one species. However, 20 families belong to Angiosperms, yielded 75 species, the Dicotyledons represented by 16 families, while Monocotyledons represented by four families. The annuals represented by 60 species (78.94%), perennial herbs by 10 species (13.15%) while trees and shrubs represented by six species (7.89%) from the total number of species in the forest. Among the dominate important species 2 species of high grazing value, 2 species of medium grazing value, and 56 species of low grazing value. In addition to 7 species of poisonous plants inhabited the forest